(untitled) (Fiep Bulletin - online, 2019)
Abstract: The objective was to analyze the presence of children in places of sport competition in the 2016 Olympics,aiming the development of the sport, under the theoretical approach of a systemic model. The study was characterized asobservational and prognostic. Subjects were children who were in the entry lines of certain competitions and arenas of the Rio2016 Olympics. Data were analyzed based on the systemic model of Bronfenbrenner (1996). Only a small number of childrenwere observed in relation to the adult public. The participation of children as agents of diffusion of different modalities that are nottraditional in Brazil, in the school and out-of-school environment, could instigate the participation of children in these modalities.They could be developed in sports schools, in physical education classes, in a multidisciplinary and interdisciplinary way withother curricular subjects, involving the school pedagogue, in sports program-projects, in a larger context involving the students’families, as well as public and private bodies, expanding the sports culture in our country, through opportunities and lifestylesfavorable to the development of different Olympic modalities in Brazil.